The cognitive neuroscience of memory : an introduction - Eichenbaum, Howard (Oxford University Press, 2002)
This clear and accessible textbook aims to introduce students to the brain's remarkable capacity for memory. It assumes little background knowledge from biology or psychology and is intended for use in graduate courses.